Tétanos du post-partum sur déchirure vaginale à propos d’un cas à l’Hôpital National de Zinder, Niger - Mahamadou Doutchi; Harissou Adamou; Ibrahim Amadou Magagi; Amadou Magagi; Souleymane Oumarou Garba; Abdoul Azize Garba (European Scientific Journal, ESJ, 2017)
We report an exceptional case of postpartum tetanus occurring in an unvaccinated primipara having given birth in a health center. Six days after childbirth, she had a trismus associated with generalized muscle contractions suggestive of tetanus. Obstructed labor was complicated by a vulvar tear repaired with wires under septic conditions. Functional sequelae, such as dysarthria, quadriesteria, and a decrease in visual acuity, marked the evolution. The newborn was free from neonatal tetanus. Our patient poses the problem of access to preventive care and the quality of care in health facilities in developing countries.